Selected Factors Influencing Missouri School-Based Agricultural Educators to Instruct Agricultural Mechanics Curriculum - Saucier, Ryan G.; Krysher, Sheyenne (Journal of Agricultural Systems, Technology, and Management, 2014)
The National Research Agenda for Agricultural Education and Communications suggests that teachers promote “highly effective educational programs [that] meet the academic career and developmental needs of diverse learners in all settings and at all levels” (Doerfert, 2011, p. 24). The purpose of this census survey was to determine the factors influencing Missouri school-based agricultural educators to instruct the curriculum found within the course Agricultural Construction 1 and/or 2. Data were collected via Hosted Survey™ from all teachers who instructed this course during the 2009-2010 academic school year (N = 257). The majority of the respondents chose to teach the curriculum areas found within the course; however Project Construction curriculum was the most commonly taught curriculum area. The factor, Personal Importance, was found to be the most influential factor impacting school-based agriculture educators’ decision to teach all of the agricultural mechanics curriculum areas. Administration Importance was the least influential factor persuading teachers to instruct the agricultural mechanics curriculum areas. Researchers recommend future studies to better understand the phenomenon of curriculum instruction choice by teachers and implement professional development to increase teacher skill and pedagogy competence.